2012
DOI: 10.1007/s00210-012-0772-9
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin exerts anti-inflammatory and anti-allergic effects in ovalbumin-induced murine model of allergic airway disease

Abstract: Sitagliptin, a new oral glucose lowering medication, is used for treatment of type 2 diabetes mellitus. The anti-inflammatory property of sitagliptin is reported, yet no studies have been done on asthma. In the present study, the effect of sitagliptin on allergic asthma was investigated using ovalbumin (OVA)-induced asthma model in mice. Swiss male albino mice sensitized and challenged to ovalbumin were treated with sitagliptin (8 mg/kg administered orally twice a day). Drug treatment was done on each day from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
5
20
0
Order By: Relevance
“…For dexamethasone, this was in agreement with the reports of Reber et al [24] and Herbert et al [25] who demonstrated that after short-or long-term therapy with dexamethasone there was a reduction in the total number of cells and eosinophils in BAL fluid in murine model of asthma. Also it was previously reported by Nader et al [16] that sitagliptin-treated mice had significantly reduced lung eosinophilia in BAL fluid and lung tissue as compared to OVA challenged mice in acute allergic asthma. The relationship between airway inflammation and airway remodeling was found to be complex.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…For dexamethasone, this was in agreement with the reports of Reber et al [24] and Herbert et al [25] who demonstrated that after short-or long-term therapy with dexamethasone there was a reduction in the total number of cells and eosinophils in BAL fluid in murine model of asthma. Also it was previously reported by Nader et al [16] that sitagliptin-treated mice had significantly reduced lung eosinophilia in BAL fluid and lung tissue as compared to OVA challenged mice in acute allergic asthma. The relationship between airway inflammation and airway remodeling was found to be complex.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, sitagliptin inhibited immediate-type hypersensitivity allergic reaction through inhibition of histamine release and proinflammatory cytokine production in rat peritoneal mast cells [15]. It has been demonstrated in an acute murine model of bronchial asthma that sitagliptin can enhance antioxidant status and downregulate some inflammatory cytokines expression through exerting antiinflammatory/immunomodulatory activities [16]. In this study, using a chronic model of allergic airway inflammation with subepithelial fibrosis, the effect of sitagliptin on underlying mechanisms potentially involved in airway inflammation and remodeling was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Cardio protective effect of sitagliptin may be due to reduction in inflammatory markers by down-regulation of COX-2 expression [47] and iNOS expression [48], decreasing free radicals [49] and nitro oxidative stress parameters (MDA and NOx) by increase SOD activity [50].…”
Section: Discussionmentioning
confidence: 99%
“…Nader et al (2012) have shown that NO content as well as the mRNA expression of iNOS was remarkably decreased by sitagliptin treatment in murine model of allergic airway disease.…”
Section: Ajptmentioning
confidence: 96%